2020
DOI: 10.1017/dce.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing and evaluating predictive conveyor belt wear models

Abstract: Conveyor belt wear is an important consideration in the bulk materials handling industry. We define four belt wear rate metrics and develop a model to predict wear rates of new conveyor configurations using an industry dataset that includes ultrasonic thickness measurements, conveyor attributes, and conveyor throughput. All variables are expected to contribute in some way to explaining wear rate and are included in modeling. One specific metric, the maximum throughput-based wear rate, is selected as the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…To achieve robust validation, data from at least one (preferably more than one) industry partner are required. However, a recent review of process system failure and reliability literature reports that "collaborative works between industry and academia are observed to be rare" (Amin et al, 2019) and we have shown elsewhere that few published models in this field are validated using industry data (Webb et al, 2020). We suggest that datasharing in the field of EAM is sufficiently problematic as to be reducing the progress of the field by restricting researchers' access to data required to develop effective models for asset life prediction and to improve maintenance management practice.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…To achieve robust validation, data from at least one (preferably more than one) industry partner are required. However, a recent review of process system failure and reliability literature reports that "collaborative works between industry and academia are observed to be rare" (Amin et al, 2019) and we have shown elsewhere that few published models in this field are validated using industry data (Webb et al, 2020). We suggest that datasharing in the field of EAM is sufficiently problematic as to be reducing the progress of the field by restricting researchers' access to data required to develop effective models for asset life prediction and to improve maintenance management practice.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, individuals are less likely to want to share data if it is labor-intensive to do prepare (Borgman, 2012). As noted earlier EAM data come from numerous data sources and is often very difficult to aggregate and assimilate (Webb et al, 2020). Some of it can even be kept in proprietary systems and thus not possible to extract in an appropriate form.…”
Section: Concerns In Data Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-destructive testing (NDT) of conveyor belts gives vast possibilities related to optimization of the belt conveyor maintenance costs, through choosing the right moment for repair, replacement or recondition of the belt based on, among others, detected damage [1] or the rate of change of belt thickness [2]. Belt operating time depends on several factors that were presented in the article [2]. NDT research use, inter alia, analysis of the magnetic field changes generated by damaged or missing cords.…”
Section: Introductionmentioning
confidence: 99%
“…The non-destructive testing (NDT) of conveyor belts gives vast possibilities related to the optimization of conveyor belt maintenance costs, such as choosing the right moment for repair, replacement or recondition of the belt based on, among other factors, detected damage [1] or the rate of change of belt thickness [2]. Belt operating time depends on several factors that are presented in the literature [2]. Among other things, it is affected by the hardness, size and shape of transported materials, the specificity of transport point and the length and age of belt cord.…”
Section: Introductionmentioning
confidence: 99%